Disinformation, International Relations, And The 2024 Indonesia’s Election - Yusnan Hadi Mochtar; Ramdan Lamato (Journal of Science and Research, 2026)
Southeast Asia is highly vulnerable to electoral disinformation. Previous studies reveal that such campaigns are often driven by actors endorsed by political parties, as observed in Indonesia and Malaysia. While this perspective is relevant, a more nuanced understanding is required to grasp the complexity of disinformation, particularly where domestic and international dimensions intersect. This research contributes to this understanding through an Indonesian case study. Notably, disinformation in previous Indonesian elections has involved international elements, such as false narratives during the 2019 presidential election alleging cooperation between the Indonesian Communist Party and China to secure Joko Widodo’s victory. Building on this precedent, this study explores the extent to which international dimensions were exploited for disinformation during the 2024 election. Employing a qualitative methodology, this research analyzes data collected from public discussions, academic journals, books, institutional reports, and news media. The article presents three layers of analysis. First, it identifies specific instances of disinformation related to international issues during the election. Second, it investigates the actors propagating this disinformation and their underlying motives. Finally, the study demonstrates the challenges inherent in combating this problem. Ultimately, this research concludes that international issues were actively exploited for disinformation during Indonesia’s 2024 election. It further underscores the need for International Relations (IR) scholarship to devote greater attention to the nexus of domestic and international spheres, and to recognize the capacity of ‘micro’ actors in spreading disinformation.